Potential toxic effect on aquatic fauna by the dwarf shrub Empetrum hermaphroditum - Brannas, E.; Nilsson, M. C.; Nilsson, L.; Gallet, C.; Brannas, K.; Berglind, R.; Eriksson, L. O.; Leffler, P. E.; Zackrisson, O. (HAL CCSD, 2004)
International audience The common evergreen dwarf shrub Empetrum hermaphroditum has influence on the functioning of boreal terrestrial ecosystems in northern Sweden. The negative effects of E. hermaphroditum are partly attributed to the production of the dihydrostilbene, batatasin-III, which is released from leaves and litter by rain and snowmelt. In this study, we investigated whether batatasin-III is carried by runoff into streams and lakes during the snowmelt period and whether it is also potentially hazardous to aquatic fauna. Sampling of water from streams and a lake for which the surrounding terrestrial vegetation is dominated by E. hermaphroditum was done during the snowmelt period in May 1993 and in 1998, and analyzed for batatasin-III. Using 24- and 48-hr standard toxicity tests, we analyzed toxicity to brown trout ( Salmo trutta) alevins and juvenile water fleas ( Daphnia magna). Toxicity ( proportion of dead individuals) to trout was tested at pH 6.5 and compared with that of a phenol within a range of concentrations. In the toxicity ( proportion of immobilized individuals) test on D. magna, the interactive effect of pH ( pH 5.5 - 7.0) was included. Concentration of batatasin-III was generally higher in 1998 than in 1993 and showed peak levels during snowmelt. Concentration in ephemeral runnels > the lake > streams running through clear-cuts dominated by E. hermaphroditum > control streams lacking adjacent E. hermaphroditum vegetation. The maximum concentration of batatasin-III found was 1.06 mg l(-1). The proportion of dead yolk sac alevins increased significantly (P < 0.001) with increasing concentrations of batatasin-III and time of exposure. After 24 hr, EC50 was 10 mg l(-1). It was 2 mg l(-1) after 48 hr. The effect of phenol was negligible, indicating a specific phytotoxic effect of the bibenzyl structure of batatasin-III. The proportion of mobile D. magna became significantly smaller ( P < 0: 001) with increasing concentrations of batatasin-III, with decreasing pH, and with ...